Evidence for Coupling Between the Subseasonal Oscillations in the Southern Hemisphere Midlatitude Ocean and Atmosphere. Issue 4 (10th February 2021) - Xue, Daokai; Lu, Jian; Qian, Yun; Zhang, Yaocun
Abstract: A regional perspective is taken to investigate the intriguing ∼25‐day periodicity in the Southern Hemisphere (SH) baroclinic annular mode (BAM) and the possible underlying mechanisms. Results show that the 25‐day periodicity exists not only in the zonal average but also in the regional average of eddy activity as long as the domain of the average is wide enough to accommodate a wave packet. The favorable domain for the ∼25 days periodicity is located downstream of the largest baroclinicity in midlatitudes. The wave activity developed there can travel circumglobally several times with a typical group velocity of 25 m s −1, and reenter the domain every 12.5 days, setting the base periodicity. A slower oceanic oscillation at a time scale of ∼100 days in the same region appears to select and reinforce the multiples of 12.5 days, giving rise to a pronounced ∼25‐day periodicity in the wave activity. Plain Language Summary: Storm track is the most prominent feature in the midlatitude atmosphere and recent studies found a marked ∼25‐day periodicity in its variability in the Southern Hemisphere (SH) and the associated hydrometeorological fields. However, the annular nature in the baroclinic annular mode (BAM) renders it difficult to extract the regional climate predictability this periodicity may bring. Zooming into the Indo‐western Pacific sector in the SH, we found similar periodic behavior in a sectoral average of storm activity, suggesting annularity is not a necessary condition for the ∼25‐day periodicity to exist. Moreover, the regional approach leads to a new perspective on this periodic behavior: midlatitude wave packets grow in the sector of maximum midlatitude baroclinicity and get fully developed downstream thereof. These waves travel eastward at a speed of ∼25 m s −1 and thus it takes about 12.5 days for them to travel around the globe and reenter their birth place to get reinvigorated. The second reentry (i.e., ∼25 days later) of these waves can get amplified by the warm phase of the ∼100 days oscillation in the ocean, giving rise to the ∼25‐day periodicity. Key Points: Significant 20–30‐day periodicity is detected in the regional representation of baroclinic annular mode A ∼100 days oscillation in Southern Ocean SST and its selective interference with BAM is discovered The 20–30‐day periodicity of the wave activity in the main development region can lead to predictability of precipitation downstream at intraseasonal scale